Biofunctionalization of magnetite nanoparticles with stevioside: effect on the size and thermal behaviour for use in hyperthermia applications. (1st January 2019) - Gupta, Ruby; Sharma, Deepika
Abstract: Controlling the magnetic properties of a nanoparticle efficiently via its particle size to achieve optimized heat under alternating magnetic field is the central point for magnetic hyperthermia-mediated cancer therapy (MHCT). Here, we have shown the successful use of stevioside (a natural plant-based glycoside) as a promising biosurfactant to control the magnetic properties of Fe3 O4 nanoparticles by controlling the particle size. The biocompatibility and cellular uptake efficiency by rat C6 glioma cells and calorimetric magnetic hyperthermia profile of the nanoparticles were further examined. Our finding suggests superior properties of stevioside-coated magnetite nanoparticles in comparison to polysorbate-80 and oleic acid coated nanomagnets as far as particle size reduction, biocompatibility, hyperthermic effect, and cellular uptake by the glioblastoma cancer cells are concerned. The stevioside-coated nanomagnets exhibiting the maximum temperature rise were further investigated as heating agents in in vitro magnetic hyperthermia experiments (405 kHz, 168 Oe), showing their efficacy to induce cell death of rat C6 glioma cells after 30 min at a target temperature T  = 43 °C.